Modalități de stimulare și motivare a muncii - Postolachi, Valentina (Calitatea Vieții, 2015)
The transition to a democratic society depends largely on changing attitudes and behavior, on new attitudes, on the introduction and use of new methods and principles, which are accompanied by new forms of labor motivation. The emergence of new needs and individual values increases the role of the human factor, which becomes decisive and strategic in the same time, as an institution will work efficiently only when the human potential will be effectively motivated.